Three Paradigms for Learning Mathematics with the Aid of Artificial Intelligence: A Phenomenological Study of Prospective Teacher Students - Syfa Nurfadilah; Gifa Nur Arofah; Toto Subroto; Tonah (International Journal of Educational Research Excellence, 2024)
The 21st century has seen rapid changes in educational practices, mainly due to technological advancements such as artificial intelligence. Especially in today’s digital age, technology is essential in transforming education. One prominent innovation is the use of AI in the context of learning. This research aims to discover prospective teachers’ learning processes using AI. In addition, this research seeks to determine the position of AI in learning mathematics for prospective teachers. The participants are Mathematics Education students of Universitas Swadaya Gunung Jati (UGJ) Cirebon. This qualitative study uses phenomenological methods by collecting data from each research subject about experiences regarding the use of AI in solving several math problems. This research provides insight into how prospective teachers can utilize AI technology in the mathematics learning process. In addition, this research is essential because it contributes to the development of technology-based pedagogy, a significant trend in global education today. This research uses data collection methods through observation, interviews, and content. The results of this study are that 3 paradigms from previous research are in line with the theory of 3 paradigms: (1) AI-directed students as recipients, (2) AI-supported students as collaborators, and (3) AI-empowered students as leaders. Most participants in this study were collaborators in these three paradigms.